18F-fluorodeoxyglucose uptake in tumor. - Khan, N AS; Islam, MM; Mahmood, S; Hossain, GA; Chakraborty, RK (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 332-342 The abstract of this article is available on the PubMed website